An Artificial Intelligence Approach for Expurgating Edible and Non-Edible Items - Kumar, Dilip; Bansal, Urvashi; Alroobaea, Roobaea S.; Baqasah, Abdullah M.; Hedabou, Mustapha (Frontiers in Public Health, 2022)
In the pandemic of Covid 19, it is crucial to consider the hygiene of the edible and non edible things as it could be dangerous for our health to consume infected things. Furthermore, everything can not be boiled before eating as it can destroy fruits and essential minerals and proteins. So, there is a dire need of a smart device which could sanitize edible items. The Germicidal UVC has proved the capabilities of destroying viruses and pathogens found on the surface of any objects. Although, a few minutes exposure of the UVC can destroy or inactivate the viruses and the pathogens, but few doses of UVC light may damage the proteins of edible items and can affect the fruits and vegetables. To this end, we have proposed a novel design of a device which is employed with Artificial Intelligence along with UVC to auto detect edible item and act accordingly. This causes different amount of UVC doses to be applied on different items according to their permissible limit. Additionally, the device is employed with a smart architecture which leads to consistent distribution of UVC light on complete surface of edible item. This results in saving the health as well as nutrition of edible item.